Innovations in Science Learning in Inclusive Schools through the UDL Framework and Adaptive Media: A Systematic Literature Review - Emi Palupi; Sukinah; Ishartiwi (Jurnal Penelitian Pendidikan IPA, 2026)
Implementing inclusive education in science classrooms requires instructional transformations that can accommodate diverse learning modalities. This study aims to analyze trends, challenges, and instructional innovations in inclusive science education, focusing on the Universal Design for Learning (UDL) framework and adaptive media for students with special needs. The methodology employed is a Systematic Literature Review (SLR) guided by the PRISMA protocol. A total of 15 peer-reviewed articles published between 2018 and 2026 indexed in Sinta and Scopus were analyzed. The thematic synthesis indicates that the integration of UDL and adaptive digital media—such as interactive e-modules, virtual laboratories, and 3D manipulative models—significantly reduces cognitive load and enhances students' conceptual understanding and science process skills. The analysis reveals that UDL combined with local context-based learning achieves the highest instructional efficacy (40%). However, disparities in teachers' pedagogical competencies and inaccessible physical laboratory infrastructures remain critical challenges. This study recommends continuous collaborative professional development between science teachers and special education professionals to foster an accessible science learning ecosystem